2016
DOI: 10.21608/eajbsf.2016.17136
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroids Resistance Mechanism in Egyptian Cotton Leafworm Spodoptera littoralis (Boisd.)

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In Spodoptera littoralis exposure to pyrethroids was accompanied by a significant change in biological (larval duration, pupal duration, adult longevity, fecundity and fertility) and biochemical (total carbohydrates, and total lipid contents) aspects of treated larvae. It also caused significant changes in the enzyme activity of the treated larvae (Rasheed et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Spodoptera littoralis exposure to pyrethroids was accompanied by a significant change in biological (larval duration, pupal duration, adult longevity, fecundity and fertility) and biochemical (total carbohydrates, and total lipid contents) aspects of treated larvae. It also caused significant changes in the enzyme activity of the treated larvae (Rasheed et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Synthetic pyrethroids were developed to enhance the natural insecticide pyrethrum's specificity, persistence, and activity. The pyrethroids are a toxin, secondarily causing adverse effects, because of neuronal hyperexcitability (Rasheed et al, 2016). The nerve excitation occurs because of changes in nerve membrane permeabilities to sodium and potassium ions (Narahashi, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rawi et al [59] found that the treatment of EMs mildly decreased the total protein. Moreover, many researchers reported the effect of bioinsecticides and insect growth regulators on the developmental stages of S. littoralis [60].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on development of resistance of cotton leafworm against certain insecticides, treating larvae with Spinetoram for six generations caused an elongation in larval period and the last larval instar could not develop to pupae and died as permanent larvae. When the larvae were treated with Emamectin or Chlorpyrifos , they could not develop to pupae and the phenomenon of permanent larvae was appeared from the first generation, while in case of Lambda-cyhalothrin it was recorded in the second generation (Rasheed 2017, Rasheed et al 2015and Rasheed et al 2016 . This work aimed to explain this phenomenon as a result of treating the cotton leafworm, S. littoralis larvae with Spinetoram pesticide.…”
Section: Introductionmentioning
confidence: 99%